2022
DOI: 10.3390/en15030802
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Energy Policies on the Energy Efficiency Performance of Residential Properties in Portugal

Abstract: The effect of energy policies on the energy performance of residential properties/houses in nineteen Portuguese districts from 2014 to 2021 was investigated. A linear random-effects model regression was used as the method in this empirical investigation. The empirical results indicated that the income per capita has a negative effect on residential properties with high energy efficiency certificates (e.g., A+, A, and B) and a positive impact on residential properties with low energy efficiency certificates (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 63 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…Higher GDP levels tend to be associated with greater investments in energy efficiency in homes. Several studies support the use of per capita GDP as a variable to explain energy efficiency in houses, including Gamtessa [72], Hamilton et al [73], Hamilton et al [74], Tovar [75], Koengkan et al [76], and Fuinhas et al [77]. These authors have found that higher income levels and a higher proportion of elderly household members are positively associated with energy efficiency retrofit investments.…”
Section: Direção-geral De Estatísticas Da Educação E Ciência [86]mentioning
confidence: 95%
See 2 more Smart Citations
“…Higher GDP levels tend to be associated with greater investments in energy efficiency in homes. Several studies support the use of per capita GDP as a variable to explain energy efficiency in houses, including Gamtessa [72], Hamilton et al [73], Hamilton et al [74], Tovar [75], Koengkan et al [76], and Fuinhas et al [77]. These authors have found that higher income levels and a higher proportion of elderly household members are positively associated with energy efficiency retrofit investments.…”
Section: Direção-geral De Estatísticas Da Educação E Ciência [86]mentioning
confidence: 95%
“…Meanwhile, several other authors, such as Hamilton et al [73], Hamilton et al [74] and Tovar [75], have also linked higher income levels with increased energy efficiency. However, Koengkan et al [76] and Fuinhas et al [77] have identified that the impact of income on the energy efficiency of housing varies. In the highest-efficiency housing categories (A+, A, and B), income has a negative and significant impact, whereas in the lowest-efficiency categories (C, D, and E), it has a positive and significant impact.…”
Section: Social and Economic Aspects And Energy Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Energy-intensive enterprises' green innovation can lead to the value of a corporate competitive advantage and increase corporate value. Energy-intensive enterprises' ecofriendly product and process innovations can minimize the enterprise firm's waste and improve energy efficiency through recycling and reuse, while also improving the firm's economic and social performance by reducing waste and costs [7,30]. Recent research proposes that green innovation can drive environmental performance, and environmental performance relies on the value of eco-friendly materials, environmental procedures, new product development, and the inclusion of environmental sustainability concerns in corporate activities and product innovation [31].…”
Section: Green Innovation Performancementioning
confidence: 99%
“…On the other hand, the PO SEUR strategy was strongly aligned with the EU Strategic Energy Technology Plan [33] to promote new sources of renewable energy and the improvement in the energy efficiency of several public utility buildings. This is particularly relevant for Portugal since the residential sector is one of the primary energy-consuming domains in Portugal [34]. Another policy supported by PO SEUR was integrated forest management with the goal of combating forest fires in Portugal [35].…”
Section: Main Policy Impacts Of Po Seurmentioning
confidence: 99%